Design of a continuous concrete filled steel tubular column in fire. (October 2018) - Ukanwa, Kingsley U.; Clifton, G. Charles; Lim, James B.P.; Hicks, Stephen J.; Sharma, Umesh; Abu, Anthony
Abstract: Concrete filled steel tubular (CFST) columns used in multi-storey buildings are generally designed as continuous members. The fire behaviour is predicted based on the results of experimental standard fire testing of CFST members where the same temperature is applied to the column over the full column height. Over the past 36 years, 238 experimental tests have been reported in the literature on CFST columns; different types of concrete infill have been considered: plain, steel fibre and bar reinforced concrete. In these tests, the columns were loaded axially under either concentric or eccentric load, and subjected to the standard ISO 834 fire or its equivalent in a furnace. This paper has focused on the in-depth analysis of behaviour of a continuous CFST columns in fire and provided a simple design procedure to calculate the axial capacity of the CFST columns at elevated temperature. The examples given in the later section gives a step by step design procedure for practicing engineers to calculate the axial capacity of both concentrically and eccentrically loaded CFST columns in fire. Highlights: Steel fibres can be used as an alternative to bar reinforcement in CFST columns. A new proposed design procedure can be used to predict the axial capacity of CFST columns in fire. The design procedure in the AS/NZS 2327 gives a higher percentage of unsafe prediction of the axial capacity of CFST columns in fire.